Bioactive Peptide Brush Polymers via Photoinduced Reversible‐Deactivation Radical Polymerization - Sun, Hao; Choi, Wonmin; Zang, Nanzhi; Battistella, Claudia; Thompson, Matthew P.; Cao, Wei; Zhou, Xuhao; Forman, Christopher; Gianneschi, Nathan C. (Angewandte Chemie International Edition, 2019)
Harnessing metal‐free photoinduced reversible‐deactivation radical polymerization (photo‐RDRP) in organic and aqueous phases, we report a synthetic approach to enzyme‐responsive and pro‐apoptotic peptide brush polymers. Thermolysin‐responsive peptide‐based polymeric amphiphiles assembled into spherical micellar nanoparticles that undergo a morphology transition to worm‐like micelles upon enzyme‐triggered cleavage of coronal peptide sidechains. Moreover, pro‐apoptotic polypeptide brushes show enhanced cell uptake over individual peptide chains of the same sequence, resulting in a significant increase in cytotoxicity to cancer cells. Critically, increased grafting density of pro‐apoptotic peptides on brush polymers correlates with increased uptake efficiency and concurrently, cytotoxicity. The mild synthetic conditions afforded by photo‐RDRP, make it possible to access well‐defined peptide‐based polymer bioconjugate structures with tunable bioactivity. Empowered by light: Photoinduced reversible deactivation radical polymerization (photo‐RDRP) enabled access to a new class of bioactive peptide brush polymers. Those peptide‐based brush polymers exhibited well‐defined structures and tunable bioactivities, highlighting their immense potential in biomedical applications.